Seroprevalence of Toxoplasma gondii, rubella and Cytomegalovirus among pregnant females in north-western Turkey. Issue 5 (3rd September 2015) - Aynioglu, A.; Aynioglu, O.; Altunok, E. S.
Abstract : Objective:: To examine the sero-prevalence rates of Toxoplasma gondii, rubella and Cytomegalovirus (CMV) among pregnant women in different age groups in the context of a comparison with nationwide and international data previously reported. Methods:: Females of reproductive age attending to our hospital between 1 January 2012 and 1 January 2014 were included in this study. Antibodies against T . gondii, rubella and CMV were assayed using chemiluminescence immunoassay methods. The test results were evaluated retrospectively. Results:: Of the participants, 2.5 and 43.9% were seropositive for Toxoplasma IgM and IgG, respectively. The corresponding figures for rubella and CMV were 1.5 and 93.8%, and 2 and 91.5%, respectively. Conclusion:: The high rates of immunity against rubella and CMV infections among pregnant females in our region call into question the routine screening of pregnant females for these two diseases. On the other hand, the high rate of seronegativity for T . gondii warrants such a routine practice.